Space and place in the healing of life: towards a theology of affirmation in pastoral care and counselling - Louw, D. J. (Verbum et ecclesia, 2008)
How should healing be viewed and what is the contribution of Chrsitian spirituality to the dimension of pastoral therapy and the healing of life? It is argued that pastoral care should supplement the traditional cura animarum with a cura vitae. In this regard the therapeutice value of place and space is explored. A pastoral model for the making of a pastoral diagnosis is proposed wherein a theology of affirmation plays a pivotal role.